Low carbon learning: Logical framework in learning process at elementary schools. Issue 1 (April 2021) - Hudha, M N; Hamidah, I; Permanasari, A; Setiani, P; Kustiawan, I; Rachman, I; Abdullah, A G
Abstract: This study aims to identify learning content of low carbon at elementary school level in Indonesia. The method employed in this study was a combination between systematic literature review and content analysis. The results showed that low carbon content at elementary schools was mapped and presented in a simple structure so that the substantial aspects of the learning was easier to understand by the elementary school students. It has also been proven that low carbon learning content was beneficial to develop in learning within elementary school context as it trained the students to get used to living in low carbon since early ages.